Association of glymphatic system dysfunction with cognitive impairment in temporal lobe epilepsy - Wang, Jiajia; Xia, Xiaona; Zhang, Bin; Ma, Xiaotian; Shi, Feng; Wei, Ying; Li, Ling; Meng, Xiangshui (Frontiers in Aging Neuroscience, 2024)
Objectives To explore the relationship between glymphatic dysfunction and cognitive impairment in unilateral temporal lobe epilepsy (TLE). Methods This study retrospectively included 38 patients with unilateral TLE and 26 age- and gender-matched healthy controls (HCs). The diffusion tensor image analysis along the perivascular space (DTI-ALPS) index, choroid plexus volume (CPV), and cognitive assessment were obtained for each participant. Neuropsychological test batteries included Montreal Cognitive Assessment (MoCA), Minimum Mental State Examination, Arithmetic Test (AT), Digit Symbol Substitution Test (DSST), Digit Span Test (DST), Boston Naming Test, Block design, Phonological Fluency Test (PFT), and Semantic Verbal Fluency (SVF). Results Compared to HCs, TLE patients had lower scores of MoCA, AT, DSST, DST, Block design, PFT and SVF (all p < 0.05) and lower values of mean DTI-ALPS index (1.491 ± 0.142 vs. 1.642 ± 0.123, p < 0.001). Significantly lower DTI-ALPS index values were observed in the ipsilateral hemisphere than in the contralateral hemisphere (1.466 ± 0.129 vs. 1.517 ± 0.175, p = 0.013) for patients with unilateral TLE. Correlation analyses found that SVF performance was significantly or borderline significantly associated with glymphatic function (FDR-corrected p < 0.05 for all DTI-ALPS index and FDR-corrected p = 0.057 for CPV) in TLE patients. Linear regression analyses showed that increased CPV and decreased DTI-ALPS index were independent risk factors for semantic fluency impairment (all p < 0.05). Furthermore, mediation analyses found the mediator role of the mean DTI-ALPS index in the relationship between choroid plexus enlargement and semantic fluency impairment (indirect effect: β = −0.182, 95%CI = −0.486 to −0.037). Conclusion These findings reveal the important role of the DTI-ALPS index and CPV in SVF performance in unilateral TLE. Decreased DTI-ALPS index and increased CPV are the independent risk factors for semantic fluency impairment. The DTI-ALPS index may fully mediate the relationship between CP enlargement and SVF performance. These insights provide a radiological foundation for further investigations into the mechanism of the glymphatic system in TLE pathophysiology.